The use of ELMO helmets for the treatment of patients with COVID-19: experience report - Belarmino, Adriano da Costa; Pinho, Cleiton Machado; Rodrigues, Maria Eunice Nogueira Galeno; Freitas, Alisson Salatiek Ferreira de; Cunha, Larissa Alves; Ferreira Júnior, Antonio Rodrigues (Revista de Enfermagem da UFPI, 2023)
Objective: to describe nurses’ experience with the use of the ELMO helmet for the treatment of patients with COVID-19. Methods: experience report in an emergency care unit located in a metropolitan city of Ceará, Brazil, in the period from March 15 to June 22, 2021. Content Analysis was used for organization and analysis through references in the area. Results: the potentialities of care during the ELMO helmet use were observed, such as a decrease in indications for orotracheal intubation, improvement in respiratory distress, and decrease in morbidity, but also weaknesses such as diminished patient-healthcare professional communication, need for careful evaluation of the time of use and patient response, risk of psychological instability, and risk of broncho-aspiration; moreover, health teams collaborative aspects such as increased intra-team communication, effective interaction, and greater decision-making were registered. Conclusion: important results in treating COVID-19 can result from the use of this tool; however, there is a need for strict monitoring in order to avoid major respiratory complications as well as physical and psychological sequelae from the wearing of ELMO.